From Bean to Brand: Decoding the Mechanisms of Trust and Engagement in Generation Z's Purchase Decisions - Kun Peng Xia; Yong Yu Lee; Kong Miu Ling Kimberley; Mei Yee Kong; Su Hua Khor; Jia Xian Kong; Kirrthana A/P Ramachandran; Shravan Kumar; Anees Janee Ali; Daisy Mui Hung Kee (AIBPM Publisher, 2025)
Focusing on Generation Z consumers in Malaysia, this study investigates the role of brand awareness in shaping customer loyalty and purchase intention for Starbucks. The research method involved a multi-stage sampling procedure targeting Generation Z consumers in Malaysia (born 1997–2012) with recent Starbucks purchase experiences, using a pretested online survey to collect 101 valid responses from urban centers like Kuala Lumpur, Penang, and Johor Bahru. The results reveal that brand awareness enhances customer loyalty and fosters brand trust development. The brand trust serves as a powerful catalyst for brand engagement and customer loyalty, while brand engagement emerges as a crucial driver of both loyalty formation and purchase intentions. Customer loyalty exhibits a positive influence on purchase intention. These findings advance brand relationship theory by demonstrating the sophisticated pathways through which brand awareness influences behavioral outcomes among Generation Z consumers, highlighting the crucial mediating roles of trust and engagement. This research contributes to brand management literature by offering a nuanced understanding of how brand relationships develop among digital-native consumers while providing practical guidance for companies seeking to strengthen customer relationships in increasingly competitive markets.